Repositioning of HMG-CoA Reductase Inhibitors as Adjuvants in the Modulation of Efflux Pump-Mediated Bacterial and Tumor Resistance - Zsuzsanna Schelz; Hiba F. Muddather; István Zupkó (MDPI AG, 2023)
Efflux pump (EP)-mediated multidrug resistance (MDR) seems ubiquitous in bacterial infections and neoplastic diseases. The diversity and lack of specificity of these efflux mechanisms raise a great obstacle in developing drugs that modulate efflux pumps. Since developing novel chemotherapeutic drugs requires large investments, drug repurposing offers a new approach that can provide alternatives as adjuvants in treating resistant microbial infections and progressive cancerous diseases. Hydroxy-methyl-glutaryl coenzyme-A (HMG-CoA) reductase inhibitors, also known as statins, are promising agents in this respect. Originally, statins were used in the therapy of dyslipidemia and for the prevention of cardiovascular diseases; however, extensive research has recently been performed to elucidate the functions of statins in bacterial infections and cancers. The mevalonate pathway is essential in the posttranslational modification of proteins related to vital eukaryotic cell functions. In this article, a comparative review is given about the possible role of HMG-CoA reductase inhibitors in managing diseases of bacterial and neoplastic origin. Molecular research and clinical studies have proven the justification of statins in this field. Further well-designed clinical trials are urged to clarify the significance of the contribution of statins to the lower risk of disease progression in bacterial infections and cancerous diseases.